2012
DOI: 10.4049/jimmunol.1103012
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Nanometer-Scaled Ligand Patterns in Polyvalent Binding by Large Mannan-Binding Lectin Oligomers

Abstract: Mannan-binding lectin (MBL) is an important protein of the innate immune system and protects the body against infection through opsonization and activation of the complement system on surfaces with an appropriate presentation of carbohydrate ligands. The quaternary structure of human MBL is built from oligomerization of structural units into polydisperse complexes typically with three to eight structural units, each containing three lectin domains. Insight into the connection between the structure and ligand-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
41
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 76 publications
7
41
0
Order By: Relevance
“…Comparable results were obtained with the C-type lectin domain of MBL (Fig. 2C), as observed previously for the binding of MBL oligomers and the MBL lectin domain to mannose-conjugated BSA (52). These data suggest that the efficient binding of ficolin-1 (and of MBL) to GP requires oligomerization of the recognition protein, which promotes avidity through a multivalent interaction.…”
Section: Gp Interaction With Ficolinssupporting
confidence: 71%
See 1 more Smart Citation
“…Comparable results were obtained with the C-type lectin domain of MBL (Fig. 2C), as observed previously for the binding of MBL oligomers and the MBL lectin domain to mannose-conjugated BSA (52). These data suggest that the efficient binding of ficolin-1 (and of MBL) to GP requires oligomerization of the recognition protein, which promotes avidity through a multivalent interaction.…”
Section: Gp Interaction With Ficolinssupporting
confidence: 71%
“…Recombinant MBL, produced and purified as described previously (50), was kindly provided by NatImmune (Copenhagen, Denmark). The trimeric FBG recognition domain of ficolin-1 (FBG) and the C-type lectin carbohydrate recognition domain of MBL (MBL-CLec) were expressed in a baculovirus/insect cell system and purified as described previously (51,52). The molecular sizes of the proteins were estimated to be as follows: 388.1 kDa for ficolin-1, 305 kDa for MBL, 73.6 kDa for ficolin-1 FBG, and 49.1 kDa for MBL-CLec.…”
Section: Methodsmentioning
confidence: 99%
“…Binding of the polyvalent oligomer MBL, however, is highly sensitive to the scaling of its binding domains. Rearrangement of its ligands even in the nanometer range strongly affects its interaction (49). Hence, WTA may mediate resistance to MBL indirectly by acting as a scaffold for other glycopolymers.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, longer collagen-like regions are expected to bring more flexibility, which could facilitate interactions involving the collagen stalks. Although no structural data are available regarding soluble ficolins, recent studies using solution X-ray scattering of MBL oligomers revealed highly flexible molecules with near planar fan-like structures in some instances (42,43). Moreover, MBL bound to surface ligands was shown to adopt a stretched conformation, as shown by atomic force microscopy (44).…”
Section: Discussionmentioning
confidence: 99%